The World Bank’s Support for Subnational Governance through Conditional Grants : Lessons Learned from Brazil, Indonesia, and Tanzania - Garoni, Samuel Ruben Alexander (World Bank, Washington, DC, 2022)
This note presents lessons learned from three ongoing World Bank PforR projects in - Brazil, Indonesia, and Tanzania - which were highlighted in the Primer Conditional Grants in ‘Principle, in Practice and in Operations’. It is aimed to complement the theory presented in the primer and it targets Task Team Leaders designing WB projects with a decentralization component or that wish to include conditional grant schemes to enhance results at the local level. The projects were all launched in the past few years and reflect the current understanding of the challenges and opportunities of conditional grants.